Financial regulation and financial development in developing economies: case of South Africa - Mahlake, Lance (Graduate School of Business (GSB), 2025)
The study analyses financial regulation, specifically for the banking sector, set globally and implemented locally by different countries, and how it impacts financial development in the context of developing countries, considering the pace of reform since the 2008/9 financial crises and its technical nature. The regulatory framework affects advanced and developing economies the same and thus raises concerns on its efficiency in the later given the general level of financial development. The scope was restricted to focus on key indicators including financial development, systemic risk, equilibrium credit and bank regulation. Time series data from 2017 to 2022 was modelled using the Auto Regressive Distributed Lag technique which presented strong evidence that the leverage ratio is likely to result in a contraction in the long run trend of bank credit to the private sector-to-GDP ratio and possibly distort equilibrium credit for the economy in the long run, resulting in restricted capacity for financial development. The model presented no short-term relationships. A review of the microprudential regulatory framework may be required to achieve an optimum regulatory environment that protects and enables the country to grow and benefit from healthy development of the financial system that can foster greater financial depth and economic growth.